Posterior Maxillary Prosthetic Treatment with Molar Hemisection – A case report - Kurdi, Abil; Hidayati, Hanoem Eka (Indonesian Journal of Dental Medicine, 2018)
Background: Hemisection is an alternative treatment option for maintaining tooth with multiple root that indicated for extraction. Purpose: To reported tooth with multiple root indicated by extraction to be used as a fixed-fixed bridge abutment by extracting the infected root and maintain the healthy one. Case: A 53-year-old woman with caries in upper 1st molar teeth in mesiobuccally root that can't be maintained. Patients refuse the teeth to be extracted. Case Management: Hemisection treatment was performed on 26 mesiobuccal root, with the addition of bone graft. After the healing process, fixed-fixed bridges were made on 25, 26, 27, 28, with PFM on 25, 26, 27 and full cast crowns on 28 as the material. Discussion: Hemisection as a conservative treatment, can be an option for multiple  root teeth that has been indicated for extraction but still have root that can be maintained. Conclusion: Teeth performed by hemisection treatments can be used as abutments with attention to the selection of patients to achieve long-term success.